Jesus, history and the gospels - Moyise, S. (Faculty of Theology, University of the Free State, 2003)
This article considers the reasons why modern scholars have felt the need to go behind the four Gospels and search for the historical Jesus. After a short discussion on methodology, especially the criteria used to detect the earliest and most reliable traditions about Jesus, a number of recent proposals are discussed: Jesus as Jewish restoration prophet; Jesus as Galilean rabbi; Jesus as subversive reformer; Jesus as Jewish messiah. This diversity might suggest that the whole enterprise is misguided but there are positive gains for the Church, not least the recovery of the Jewishness of Jesus.
Keywords: Historical Jesus; Four Gospels; History